Czym jest filozofia moralna? - Malitowska, Anna (Filozofia Publiczna i Edukacja Demokratyczna, 2012)
The first part of the present article is an introduction to ethics as a branch of philosophy, as moral philosophy, or philosophical thinking about morality. In the second part of the article the author deals with the relationship between three kinds of thinking that relate to morality: descriptive empirical inquiry (descriptive ethics), normative thinking, and meta-ethical reflection.